2010
DOI: 10.1002/ange.200905829
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive, Excimer‐Controlled Molecular Beacon

Abstract: Nichtnucleosidische Chromophore im Stamm eines molekularen Leuchtfeuers („molecular beacon“) hemmen die Excimerfluoreszenz durch die Bildung eines Donor‐Akzeptor‐Komplexes (siehe Bild). Die ausgezeichnete Verringerung der Hintergrundfluoreszenz ermöglicht es, eine Ziel‐DNA oder ‐RNA in Gegenwart eines deutlichen Überschusses der Sonde nachzuweisen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 64 publications
0
49
0
2
Order By: Relevance
“…Additionally, MB should not take part in unintended target hybridization, which might affect selectivity, or interfere with formation of the hairpin structure, for example by binding to the stem sequence, which may also lead to an increase in background or loss of signal intensity. To avoid incomplete FRET or quenching in a hairpin form, Haner et al reported MB design in which signal control is accomplished by formation of a donor–acceptor (D–A) complex [86]. The stem contains incorporated pairs of pyrene or perylenediimide moieties that can interact by interstrand stacking.…”
Section: Hybridization Probesmentioning
confidence: 99%
“…Additionally, MB should not take part in unintended target hybridization, which might affect selectivity, or interfere with formation of the hairpin structure, for example by binding to the stem sequence, which may also lead to an increase in background or loss of signal intensity. To avoid incomplete FRET or quenching in a hairpin form, Haner et al reported MB design in which signal control is accomplished by formation of a donor–acceptor (D–A) complex [86]. The stem contains incorporated pairs of pyrene or perylenediimide moieties that can interact by interstrand stacking.…”
Section: Hybridization Probesmentioning
confidence: 99%
“…[11][12][13] Hence, it is not surprising that this chromophore has been extensively applied in the construction of aggregates inside and outside of double-helical DNA. [11][12][13][14][15][16][17][18][19][20] PBI derivatives have been covalently attached to oligonucleotides for the DNA-directed assembly of this dye in thermophilic foldamers, [14,15] as caps that trigger the aggregation of DNA hairpins, [16,17] for the construction of exceptionally stable triplexes, [11,18] for electron-transfer studies, [19] and for fluorescence quenching in highly sensitive molecular beacons. [20] For the incorporation of PBI as an artificial base surrogate at both internal and terminal positions in DNA, we recently presented a synthetic protocol based on automated phosphoramidite building block chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Winfree have shown that single-nucleotide mutations, insertions, and deletions in the catalyst strand can result in 10-to 300-fold reductions in its efficiency in catalyzing strand exchange [17]. These reductions in signal observed with single-nucleotide mismatches are comparable to other well-developed DNA sensors [26][27][28][31][32][33]. Consistent with these findings, we observed that when a single nucleotide was changed in the toehold region (Figure 3, inset), the mutant Trigger did not yield any peroxidase activity above background even at 150 nM concentration ( Figure 3, sample #10~12).…”
Section: Resultsmentioning
confidence: 86%